Undercut Analysis of Cylindrical Helical Circular Arc Gear - Xiaoping Huang; Linlin Zhao (Jixie chuandong)
At present, there are few in-depth analysis and detailed data on undercut of cylindrical helical circular arc gears, which affect people's accurate, specific and profound understanding of this undercut and the extensive application of the existing theories. For cylindrical helical circular arc gears, the undercut boundary equation and no undercut condition are derived， and the undercut probability as well as determination of point most easy to be undercut at tooth profile and minimum number of teeth to avoid undercut are studied in detail. When applied to the pure rolling circular arc gear and W-N circular arc gear, above results are verified and extended, and new conclusions and undercut calculation data that gear workers want to know are obtained. This study provides a theoretical basis for the non-undercut design of various mechanical parts with cylindrical circular arc teeth.